2003
DOI: 10.1093/ageing/32.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an association among age-related changes in physical, psychomotor and autonomic function

Abstract: the association between heart rate variability and coordination suggests concurrent aging of autonomic and psychomotor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
2
5
1
1
Order By: Relevance
“…Previous research has shown that HRV declines with aging, and other studies have demonstrated a slowing of physiologic responses across the age span (Boutcher, Cotton, Nurhayati, Craig, & McLaren, 1997;De Meersman & Stein, 2007;Fukusaki, Kawakubo, & Yamamoto, 2000;Leicht, Allen, & Hoey, 2003;Stein, Ehsani, Domitrovich, Kleiger, & Rottman, 1999;Ueno, Hamada, & Moritani, 2002;Wood, Hondzinski, & Lee, 2003). We saw little of this reduced responsiveness in our older subject group.…”
contrasting
confidence: 44%
“…Previous research has shown that HRV declines with aging, and other studies have demonstrated a slowing of physiologic responses across the age span (Boutcher, Cotton, Nurhayati, Craig, & McLaren, 1997;De Meersman & Stein, 2007;Fukusaki, Kawakubo, & Yamamoto, 2000;Leicht, Allen, & Hoey, 2003;Stein, Ehsani, Domitrovich, Kleiger, & Rottman, 1999;Ueno, Hamada, & Moritani, 2002;Wood, Hondzinski, & Lee, 2003). We saw little of this reduced responsiveness in our older subject group.…”
contrasting
confidence: 44%
“…Tests of physical function in older individuals have gained popularity as alternatives to traditional laboratory measures of physical fitness (7). These tests have a number of advantages because they evaluate the ability to perform activities of daily living, provide more information on functional impairment, are less susceptible to floor and ceiling effects, and are applicable to a wider range of age and fitness levels than are more traditional fitness tests (7)(8)(9).…”
mentioning
confidence: 99%
“…These tests have a number of advantages because they evaluate the ability to perform activities of daily living, provide more information on functional impairment, are less susceptible to floor and ceiling effects, and are applicable to a wider range of age and fitness levels than are more traditional fitness tests (7)(8)(9). The Reduced Continuous Scale-Physical Function Performance Test (CS-PFP10) is an adaptation of the full CS-PFP designed by Cress and colleagues (9) and is used in several physical domains and applied to a broad spectrum of abilities.…”
mentioning
confidence: 99%
“…The Soda Pop Coordination test is usually administered before and after some training regimen to demonstrate how an action has improved a person's abilities [42], [43], [44]. It can also be administered to monitor coordination skills and then compared to or used to create standardized scores [37], [45]. Examples of before and after testing include a study to identify the effects of a 10 week Tai-Chi-Soft-Ball training on the physical functional health of Chinese adults [43], a 5 week study on second graders to identify the effect of 20-30 minutes of sport-stacking on handeye coordination and reaction time [42], and a study on the effect of a weight-bearing and water-based exercise program on osteopenic women [44].…”
Section: Soda Pop Coordination Testmentioning
confidence: 99%
“…Examples of before and after testing include a study to identify the effects of a 10 week Tai-Chi-Soft-Ball training on the physical functional health of Chinese adults [43], a 5 week study on second graders to identify the effect of 20-30 minutes of sport-stacking on handeye coordination and reaction time [42], and a study on the effect of a weight-bearing and water-based exercise program on osteopenic women [44]. Examples of using standardized scores include a study on the elderly, which showed the relationship between heart rate variability and coordination [45].…”
Section: Soda Pop Coordination Testmentioning
confidence: 99%